Perencanaan Sistem Pengelolaan Kualitas Lingkungan dan Pengendalian Polutan Berkelanjutan untuk Pengembangan Ekowisata Taman Wisata Landak - Julianti Marbun; Sondang Sylvia Manurung; Ivan Andri Gunawan (Yayasan Literasi Sains Indonesia, 2026)
Landak Tourism Park is a post-mining area with potential for ecotourism development, but water-quality degradation may constrain its environmental sustainability. This study evaluates the factors affecting environmental-quality management, compares two surface-water sources, develops a conceptual clean-water treatment train, and formulates integrated pollution-control strategies. A descriptive-comparative mixed-methods design was used, combining water-quality testing of a tributary and a post-mining lake with field observation and in-depth interviews with site managers. Compliance was assessed against Class II surface-water criteria in Government Regulation of the Republic of Indonesia No. 22/2021. The tributary showed severe suspended-solids and organic pollution, with TSS of 732 mg/L, BOD of 10.3 mg/L, COD of 120 mg/L, ammonia of 0.53 mg/L, and DO of 2.70 mg/L. The lake had substantially lower TSS (6.67 mg/L), turbidity (4.91 NTU), and ammonia (<0.0089 mg/L), although BOD (7.62 mg/L), COD (64.7 mg/L), and DO (3.20 mg/L) still did not meet Class II criteria. The lake is therefore the more feasible source for further treatment. A conceptual process comprising screening, pre-sedimentation, coagulation-flocculation, sedimentation, multimedia filtration, and disinfection is proposed, supported by source protection, erosion control, wastewater management, routine monitoring, and institutional strengthening. The design must be verified through jar tests, pilot testing, and site-specific design-flow data before implementation.